2023
DOI: 10.1101/2023.01.26.525714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PortPred: exploiting deep learning embeddings of amino acid sequences for the identification of transporter proteins and their substrates

Abstract: The physiology of every living cell is regulated at some level by transporter proteins which constitute a relevant portion of membrane-bound proteins and are involved in the movement of ions, small and macromolecules across bio-membranes. The importance of transporter proteins is unquestionable. The prediction and study of previously unknown transporters can lead to the discovery of new biological pathways, drugs and treatments. Here we present PortPred, a tool to accurately identify transporter proteins and t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…At the core of these models are so-called embeddings, which encode protein characteristics into a high-dimensional numerical space suitable for many different downstream applications. In particular, recent works have shown that embeddings can be used for the identification of protein homologs, even in cases of low sequence similarity [34; 35; 36].…”
Section: Discussionmentioning
confidence: 99%
“…At the core of these models are so-called embeddings, which encode protein characteristics into a high-dimensional numerical space suitable for many different downstream applications. In particular, recent works have shown that embeddings can be used for the identification of protein homologs, even in cases of low sequence similarity [34; 35; 36].…”
Section: Discussionmentioning
confidence: 99%
“…The application of deep learning (DL) approaches to encode protein sequences has shown promising results in several tasks such as subcellular [8] and sub-organelle [9][10][11] classification, protein structure [12,13] and function prediction [14][15][16][17], and proteinprotein interactions (PPI) prediction [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…DL-based embedding predictors offer several advantages. Firstly, they do not require lengthy pre-processing steps, as only the FASTA sequence is necessary for input [9,10,17]. This simplifies the prediction process and saves time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations